2010
DOI: 10.1016/j.landusepol.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Near-shore wind power—Protected seascapes, environmentalists’ attitudes, and the technocratic planning perspective

Abstract: Link to publication Citation for published version (APA):Wolsink, M. (2010). Near-shore wind power -protected seascapes, environmentalists' attitudes, and the technocratic planning perspective. Land Use Policy, 27(2), 195-203.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 54 publications
2
99
1
Order By: Relevance
“…This idea is extremely naïve and siting issues offshore are just as relevant as onshore (Haggett, 2008). The case is analysed based on actor and process data and a survey among people that are most committed to the Wadden region, which is an internationally significant and ecologically sensitive landscape (Wolsink, 2009). The siting case on water management concerns Oolderveste, project comprising 850 mainly luxury family dwellings to be built in 2002 in within the river Meuse's floodplain southwest of the city of Roermond (Wolsink, 2006; survey by Jonk and Wolsink, 2003).…”
Section: Methods and Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea is extremely naïve and siting issues offshore are just as relevant as onshore (Haggett, 2008). The case is analysed based on actor and process data and a survey among people that are most committed to the Wadden region, which is an internationally significant and ecologically sensitive landscape (Wolsink, 2009). The siting case on water management concerns Oolderveste, project comprising 850 mainly luxury family dwellings to be built in 2002 in within the river Meuse's floodplain southwest of the city of Roermond (Wolsink, 2006; survey by Jonk and Wolsink, 2003).…”
Section: Methods and Frameworkmentioning
confidence: 99%
“…A survey among the members of the WaddenVereniging showed that a landscape that should be most protected, the WaddenSea itself, was selected to build the wind farm. The survey also showed that turbines are not considered a threat in all types of landscape, for example turbines alongside the Afsluitdijk (the 32 km long large dyke separating Wadden Sea and IJsselmeer) would have been acceptable for a majority (Wolsink, 2009). Subsequently, the WaddenVereniging applied its strategic influence to obstruct the entire project.…”
Section: Wind Power Policymentioning
confidence: 98%
“…So far we have found that coastal areas may be less expensive to produce smaller amounts of electricity than far shore areas, where resources seem unlimited, but this comes at the cost of higher cost sensitivity to planning issues including conservation and alternative area use, which can be confirmed by Wolsink [25]. They are also less sensitive to variations of investment costs.…”
Section: Sensitivity Analysesmentioning
confidence: 73%
“…The third element of the framework recognises that the implementation process of a community wind project involves multiple decisions and stages (McLaren et al, 2013) -for example, about the location of wind turbines with a given locality (Wolsink, 2010), about whether the project should receive planning permission (Cowell et al, 2011), or the fundamental choice of which technology should be utilised (Barry and Ellis, 2011). For each of these decisions, people may have expectations about who should be included, the extent of influence they should have, and the types of information that should be provided with.…”
Section: Analytical Frameworkmentioning
confidence: 99%